2019
DOI: 10.1155/2019/6246285
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Premenstrual Syndrome at Different Intervention Time: A Systemic Review and Meta-Analysis

Abstract: Background. Premenstrual syndrome (PMS) is one of the most common gynecological conditions with no standard modern therapeutic schedule. Some studies have reported the effects of acupuncture in treating PMS, but the intervention time varies. This review evaluated the efficacy of acupuncture for patients with PMS and the appropriate time to initiate acupuncture therapy. The review has been registered on the “PROSPERO” website; the registration number is CRD42018109724. Methods. A comprehensive literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…168 Two meta-analyses conducted similarly noted greater efficacy of acupuncture over placebo in pooled data. 169,170 One recent RCT of auriculotherapy failed to separate from placebo. 171 A meta-analysis and systematic review of reflexology for PMS found an overall effect for the intervention in reduction of severity of symptoms, with increased effect shown with longer duration of reflexology sessions.…”
Section: Non-pharmacological Cammentioning
confidence: 99%
“…168 Two meta-analyses conducted similarly noted greater efficacy of acupuncture over placebo in pooled data. 169,170 One recent RCT of auriculotherapy failed to separate from placebo. 171 A meta-analysis and systematic review of reflexology for PMS found an overall effect for the intervention in reduction of severity of symptoms, with increased effect shown with longer duration of reflexology sessions.…”
Section: Non-pharmacological Cammentioning
confidence: 99%
“…Partiendo de la premisa de que el TDPM y el SPM se originan gracias a los cambios en el yin-yang durante el ciclo menstrual, múltiples autores se empeñan en relacionar el efecto de la acupuntura (que precisamente busca restaurar este ciclo a través de la colocación de agujas en varias partes del cuerpo) con los desequilibrios del ciclo menstrual. Una revisión sistemática muestra que la efectividad de la acupuntura es superior a otras terapias para el TDPM (Zhang et al, 2019). Este grupo refiere que no hay cambios significativos si se aplica en cualquier momento antes o durante la menstruación.…”
Section: Medicina Alternativa Y Complementariaunclassified
“…However, you should be cautious and talk to your doctor before using herbal remedies to relieve symptoms. Some herbal supplements, such as milk thistle, can have side effects when taken with other medications [5].…”
Section: Coping With Premenstrual Dysphoric Disordermentioning
confidence: 99%